Submerged Culture of Mushrooms in Bioreactors – Challenges, Current State-of-the-Art, and Future Prospects - Li-Wen Zhu; Hong-Mei Li; Dong-Sheng Li; Ya-Jie Tang (Food Technology and Biotechnology, 2007)
Medicinal mushrooms have profound health-promoting benefits. Recently, a number of substances of mushroom origin have been isolated, identified and shown to have physiological activities, such as antitumor, immunomodulating, cardiovascular, antihypercholesterolemia, antibacterial, antiviral, antiparasitic, hepatoprotective, and antidiabetic activities. Currently, commercial products from medicinal mushrooms are mostly obtained through the field-cultivation of the fruiting body. However, in this case it is difficult to control the quality of the final product. Submerged fermentation of the mycelial form of mushroom-producing fungi has received much attention as a promising alternative for efficient production of the biomass of medicinal mushrooms and their active metabolites. However, in order for the production to be successful at industrial scale, various technical problems need to be solved, including characterization of the variations that occur during the submerged cultivation of mushrooms in bioreactors and their effects on growth and product formation. This review outlines the major factors that affect the submerged cultivation of mushrooms in bioreactors, including oxygen supply, shear and mixing, morphology and rheology, as well as two-stage cultivation strategies and high-cell-density cultivation strategies such as fed-batch fermentation.